The role of food and nutrition system approaches in tackling hidden hunger - Burchi, F.; Fanzo, J.C.; Frison, Emile A. (MDPI, 2011)
One of the World`s greatest challenges is to secure sufficient and healthy food for all, and to do so in an environmentally sustainable manner. This review explores the interrelationships of food, health, and environment, and their role in addressing chronic micronutrient deficiencies, also known as "hidden hunger", affecting over two billion people worldwide. While the complexity and underlying determinants of undernutrition have been well-understood for decades, the scaling of food and nutrition system approaches that combine sustainable agriculture aimed at improved diet diversity and livelihoods have been limited in their development and implementation. However, an integrated system approach to reduce hidden hunger could potentially serve as a sustainable opportunity.